2019
DOI: 10.1038/s41598-019-44200-8
|View full text |Cite
|
Sign up to set email alerts
|

Ras suppressor-1 (RSU-1) promotes cell invasion in aggressive glioma cells and inhibits it in non-aggressive cells through STAT6 phospho-regulation

Abstract: Most gliomas are invasive tumors formed from glial cells and associated with high mortality rates. In this study, we characterized four glioma cell lines of varying degree of aggressiveness (H4, SW1088, A172 and U87-MG) in terms of morphology, cytoskeleton organization and stiffness, and evaluated their invasive potential by performing invasion, colony forming and spheroid invasion assays. Cells were divided into two distinct groups: aggressive cell lines (A172 and U87-MG) with more elongated, softer and highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 60 publications
1
30
0
1
Order By: Relevance
“…Since the role of GDF15 in cancer progression is controversial and not fully elucidated yet [50,51], we first tested GDF15 expression in three cell lines H4, SW1088, and A172 both at the mRNA (Figure 1A) and protein level (Figure 1B,C). In our previous work [34], we have shown that A172 cells that cause GBM are very aggressive having a strong invasive capacity in contrast to SW1088 cells, which cause astrocytoma and are less invasive, and H4 cells which are almost non-invasive neuroglioma cells. Here, we show that H4 cells express GDF15 at higher levels than SW1088 and A172 cells both at the mRNA and protein level (Figure 1), whereas RSU-1 expression follows the exact opposite pattern, being elevated as the aggressiveness of cells increases (Figure 1D–F).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the role of GDF15 in cancer progression is controversial and not fully elucidated yet [50,51], we first tested GDF15 expression in three cell lines H4, SW1088, and A172 both at the mRNA (Figure 1A) and protein level (Figure 1B,C). In our previous work [34], we have shown that A172 cells that cause GBM are very aggressive having a strong invasive capacity in contrast to SW1088 cells, which cause astrocytoma and are less invasive, and H4 cells which are almost non-invasive neuroglioma cells. Here, we show that H4 cells express GDF15 at higher levels than SW1088 and A172 cells both at the mRNA and protein level (Figure 1), whereas RSU-1 expression follows the exact opposite pattern, being elevated as the aggressiveness of cells increases (Figure 1D–F).…”
Section: Resultsmentioning
confidence: 99%
“…RSU-1, which binds to PINCH1 at FA sites [19] has been previously found to be upregulated in more invasive breast and brain cancer cells [29,34]. Moreover, we recently demonstrated a differential regulation of cell migration and invasion of glioma cells by RSU-1 based on their aggressiveness, with RSU-1 promoting an invasive behavior in aggressive cells (A172 and U87-MG) and inhibiting them in the less aggressive ones (H4 and SW1088) [34]. This by itself indicates the existence of a complex molecular mechanism that governs glioma cell invasion in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, before each experiment, the cells were washed twice with PBS and new complete media was added. The petri dish (35 mm) was mounted directly on the AFM specimen disc and all the experiments were performed under liquid condition (cells' complete media) at room temperature [10,41,42]. AFM experiments: A Molecular Imaging-Agilent PicoPlus AFM system (now known as AFM 5500 Keysight technologies) with a round (2.5 μm radius) ball-shape tip (CP-PNPL-BSG), and spring constant of 0.08 N m −1…”
Section: Discussionmentioning
confidence: 99%